The Relationship Between Knowledge and Belief in Traditional Medicine Among Patients with Diabetes Mellitus - Mauliani, Dian Putri; Amal, Ahmad Ikhlasul; Melastuti, Erna; Hendrawan, Gagah Satria (Jurnal Surya, 2025)
Introduction: A majority of individuals with diabetes mellitus (DM) prefer traditional medicine due to its perceived lack of negative side effects. Patients with good knowledge tend to have high beliefs in treatments that offer minimal side effects and significant benefits. This research aims to determine the relationship between knowledge and the level of belief in traditional medicine. Methods: This quantitative study employed a descriptive analytic method with a cross-sectional approach. The population in this study were 100 DM patients with total of 80 DM patients were recruited using purposive sampling technique. Data collection performed by using valid and reliable knowledge and belief in the use of traditional medicine questionnaires. Data analysis was performed using the Spearman rank test to determine the correlation between knowledge and the level of belief in traditional medicine. Results: A total of 55 patients (68.8%) demonstrated good knowledge, and 59 patients (73.8%) exhibited high belief in the use of traditional medicine.  A significant relationship was found between knowledge of traditional medicine and the level of belief in traditional medicine, with a significance value of 0.0001 and a correlation coefficient of 0.735. Conclusion: There is a significant relationship between knowledge of traditional medicine and the level of belief in traditional medicine.  Hospital can improve healthcare services by providing education, such as increasing the number of posters about DM treatment, both traditional and medical. Keywords: Belief; Diabetes Mellitus; Knowledge; Traditional Medicine